2017
DOI: 10.1021/acs.jpclett.7b02505
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Far-Field Raman Selection Rules by Light–Plasmon Coupling Demonstrated by Tip-Enhanced Raman Scattering

Abstract: We present an experimental study on the near-field light-matter interaction by tip-enhanced Raman scattering (TERS) with polarized light in three different materials: germanium-doped gallium nitride (GaN), graphene, and carbon nanotubes. We investigate the dependence of the TERS signal on the incoming light polarization and on the sample carrier concentration, as well as the Raman selection rules in the near-field. We explain the experimental data with a tentative quantum mechanical interpretation, which takes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 72 publications
2
38
0
Order By: Relevance
“…In such cases, some Raman inactive modes can become Raman active [46]. Moreover, light-plasmon coupling in a nanocavity between the tip and the metal substrate can lead to the alteration of classical Raman selection due to photon tunneling through perturbation of the evanescent field [47].…”
Section: Surface Selection Rules Of Ters In 2d Semiconductorsmentioning
confidence: 99%
“…In such cases, some Raman inactive modes can become Raman active [46]. Moreover, light-plasmon coupling in a nanocavity between the tip and the metal substrate can lead to the alteration of classical Raman selection due to photon tunneling through perturbation of the evanescent field [47].…”
Section: Surface Selection Rules Of Ters In 2d Semiconductorsmentioning
confidence: 99%
“…Additionally, the light-plasmon coupling in TERS can also modify the classical Raman selection rules, caused by photon tunneling through perturbation of the evanescent field. [201] 6. Applications: TERS imaging of 2D materials…”
Section: = (4)mentioning
confidence: 99%
“…[36] Recently, Poliani et al reported that the plasmon enhanced Raman signal is largely independent of the incoming light polarization in several materials, due to a modification of the Raman selection rules in TERS. [201] Moreover, the study of symmetry--imposed selection rules also facilitates the understanding of linear and nonlinear optical processes in molecules and solids. [244] However, the influence of the gap-mode on the symmetry--derived selection rules for TERS still remains to be elucidated.…”
Section: Selection Rules For Tersmentioning
confidence: 99%
“…Thus, TERS probes only a few nanometers into the surface and sapphire modes are no longer detectable. [23] The spectra #2 and #3 show a tip-enhanced Raman peak located at 460 cm −1 . This peak is assigned to the A 1 (TO) phonon mode of the InGaN alloy.…”
mentioning
confidence: 98%
“…The tip is produced by electrochemical etching of a 50 µm thick gold wire. The details of the TERS setup and scattering mechanisms are described in reference [23]. The compositional homogeneity of the different In-GaN films on the micrometer scale was studied by micro-Raman mapping over an area of 10×10 µm 2 .…”
mentioning
confidence: 99%